Effects of Autism on Parent’s Mental Health: Understanding the Impact of Autism on Parent's Mental Health and Family Dynamics (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Raising a child with an autism spectrum disorder (ASD) can be an overwhelming experience for parents and families. Overall and serious disabilities frequently present in kids with ASD are related to a host of difficulties in careers, such as reduced parental effectiveness, increased family stress and an rise in mental and physical health issues compared with parents with kids with other developmental disorders. In addition to considerable financial pressure and time pressures, high divorce rates and a lower family well-being overall reinforce the burden on families with an ASD child. Such effects of the parent and family affect diagnosed children reciprocally and negatively and can also decrease the positive effects of the treatment. Neither parent nor family factors are thought to influence the immediate and long term effects of therapy. However, the majority of ASD treatments are assessed exclusively in terms of children's outcomes. Although significant changes to the diagnosed boy are not expected to relieve established parent and family distress, particularly as additional family disorder will add to the time and cost of the intervention. A new model is therefore developed for intervention evaluation that takes these considerations into account and better explains the transactional essence of these relationships.